2014 IEEE International Conference on Semiconductor Electronics (ICSE2014) 2014
DOI: 10.1109/smelec.2014.6920785
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of TMAl preflow to the properties of AlN and GaN film grown on Si(111) by MOCVD

Abstract: The influence of TMAl preflow to the AlN buffer layer and GaN thin film was studied by Optical Microscope, Atomic Force Microscope, X-ray diffraction and Transmission Electron Microscope. Different duration of TMAl preflow lead to substantially differences of the AlN buffer layer and GaN film properties in terms of surface morphology and crystal quality. It was found without TMAl preflow the crystal quality of AlN buffer layer and GaN deteriorated due to the formation of amorphous interlayer between Si and AlN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Such an observed increase can be attributed to the dielectric loss of AlN layer, which relates to the crystalline quality of the insulating AlN layer. In our previous work , the existence of SiN x at AlN/Si interface caused the degradation of AlN crystalline quality. Consequently, high threading dislocation densities in low quality AlN provide the leakage paths leading to enhanced electric field in the dielectric layer , which increases the dielectric constant of the insulating AlN and the consequent AlN capacitance, resulting in the increase of RF loss.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Such an observed increase can be attributed to the dielectric loss of AlN layer, which relates to the crystalline quality of the insulating AlN layer. In our previous work , the existence of SiN x at AlN/Si interface caused the degradation of AlN crystalline quality. Consequently, high threading dislocation densities in low quality AlN provide the leakage paths leading to enhanced electric field in the dielectric layer , which increases the dielectric constant of the insulating AlN and the consequent AlN capacitance, resulting in the increase of RF loss.…”
Section: Resultsmentioning
confidence: 93%
“…In previous work, we have reported that a SiN x interlayer could be formed at the AlN/silicon interface (Fig. a) without the pre‐flow Al at the initial step of the AlN growth on Si . The material characteristics of two samples are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GaN and AlN, and its alloys (AlGaN) heterostructures is a very interesting materials because of their applications in high-power, high-frequency field effect transistors, light-emitting diodes, and high electron mobility transistors (HEMTs) [1][2][3][4][5][6][7][8] than other materials, such as GaAs or GaP [9][10][11]. To improve the performances of these devices, the electronic properties of the twodimensional electron gas (2DEG) formed in the AlGaN/GaN quantum well is the most important factor.…”
Section: Introductionmentioning
confidence: 99%
“…The alloy of AlN and GaN and their alloy (AlxGa1-xN) have been intensively studied for decades [1][2][3][4][5][6] and they are very important materials for many applications in optoelectronic and power-electronic devices such as visible and ultraviolet light-emitting diodes, high electron mobility, solar cell, high-power electronic devices, field-effect transistor and high-speed electronic devices operating at high temperature and environments, etc. [7][8][9][10][11][12][13][14][15][16][17] AlxGa1-xN epitaxial layers are used for carrier confinement as electron blocking or barrier layers normally in laser and quantum-well ultraviolet light emitting diodes.…”
Section: Introductionmentioning
confidence: 99%